Dynamic nuclear polarization of a glassy matrix prepared by solid state mechanochemical amorphization of crystalline substances. Issue 11 (23rd December 2014) - Elisei, E.; Filibian, M.; Carretta, P.; Colombo Serra, S.; Tedoldi, F.; Willart, J. F.; Descamps, M.; Cesàro, A.
Abstract : "Solvent-free" co-milling effectively produces an intimate mixture of the solid substrate and the radical species for performing DNP. Abstract : A mechanochemical "solvent-free" route is presented for the preparation of solid samples ready to be employed in the Dynamic Nuclear Polarization (DNP). 1 H-DNP build-up curves at 3.46 T as a function of temperature and radical concentration show steady state nuclear polarization of 10% (0.5% TEMPO concentration at 1.75 K).